Strategi Pembelajaran PAI pada Siswa Tunagrahita di SLB Widya Shantika Karangploso Kabupaten Malang - Margaretta, Shinta; Hidayatullah, Muhammad Fahmi; Sulistiani, Ika Ratih (SAP (Susunan Artikel Pendidikan), 2024)
The aim of this study was to determine the effectiveness of Islamic Religious Education learning strategies for mentally disabled students. Learning strategies are methods used to make learning easier for students so that it runs in accordance with learning objectives. The purpose of writing this article is to find out PAI learning strategies for mentally retarded children at SLB Widya Shantika Karangploso. Using qualitative research carried out descriptively and in-depth by interviewing sources, then analyzing and reviewing to obtain results and conclusions. The results of the research are the strategies carried out for mentally disabled children, learning plann is carried out by preparing prota, promissory notes, syllabus and lesson plans, the learning process has 3 parts. namely preliminary, core and closing activities and summative and formative learning evaluations to determine the achievements of mentally disabled children in learning.